Simulação de frentes de choque no aglomerado de galáxias Abell 1758 - Volert, Ricardo Cezar (2022)
Galaxy clusters are considered the largest structures in the Universe and are close to a hydrodynamic equilibrium, being gravitationally bound, where they form through the merger of subclusters through collisions. The Abell 1758 cluster of galaxies (=0.279) is formed by four structures that show signs of a possible existence of a gas bridge connecting the southern and northern structures. The dynamics of A1758N has been studied on other occasions, however, recent radio observations suggest a possible interaction between A1758N and A1758S, which was previously ignored. Through hydrodynamic simulations we evaluated the plausibility of the existence of a gas bridge in A1758 in Ąve different scenarios that resulted in eleven models that could explain the cluster dynamics, where each scenario considers the approach of the north and south substructures. Thermodynamic jumps were analyzed and we evaluated whether shock fronts were present and what their intensity was. After deĄning the initial conditions and scenarios to be explored, numerous numerical simulations were performed and later analyzed through temperature and density maps, temperature proĄles, X-ray mocks and through machine learning, we obtained the successive positions of each structure and their radial velocities. Among the simulations, the best model represents a scenario of A1758S approaching A1758N after an apocentric passage, where there is a transversal shock wave with direction towards A1758S, with Mach number ℳ=1.9 and which is intermingled with an energy dissipation from the Ąrst pericentric passage in A1758N that occurred 0.22 Gyr earlier and that is heating the intracluster medium. We found through density maps the presence of a low density gas bridge that could not be easily identiĄed by X-rays. In a complementary evaluation, A1758S presents itself as a low temperature substructure, formed by two subclusters where A1758S1 (A1758WSW) has possibly more mass than A1758S2 (A1758SSW) and its current state is supposedly the result of a Ąrst pericentric passage that occurred 0.35 Gyr ago.